The Multi-Depot Travelling Salesman Problem using MATLAB Coding with Genetic Algorithm:A Case Study of Domino’s Pizza Centers - Nilofer, Ms.; Mohd.Rizwanullah, Dr. (International Journal of Engineering and Technology, 2018)
Dominos is the best pizza delivery company in the world. In current phase of business it is also having the high demand of internal consumption. The delivery boy need to cover the 12 centers which are located at different place in Jaipur. In this paper an attempt has been made to improve delivering of pizzas at twelve randomly Centers in the city. The problem is modeled as Travelling Salesman Problem. In this problem, our objective is to find the lowest tour cost of the pizzas centers, which are connected. Different paths cost is given (TSP) and it is very similar to the Assignment Problem (AP) apart from there is an further constraint i.e. Ci j =∞, if i = j. The salesman has to visit n cities. The objective in this paper is to select the method in which the cities are visit in such a way and that total travelling time is to be minimized; sometimes AP does not fulfill the further restriction, In this article we present modiﬁed one’s algorithm with MATLAB Coding with genetic algorithm for the solution of the TSP problem.